GE_GERICHTE P/3686/2011 vom 11. November 2016 - GE Cour de justice (2016)
QUALITÉ POUR AGIR ET RECOURIR ; INTÉRÊT JURIDIQUEMENT PROTÉGÉ ; PARTIE À LA PROCÉDURE ; DOMMAGE DIRECT | CP.138; CP.158; CP.163; CP.165; CPP.382; CPP.115; CPP.118